2018
DOI: 10.1111/ajo.12931
|View full text |Cite
|
Sign up to set email alerts
|

Experience and confidence in vaginal breech and twin deliveries among obstetric trainees and new specialists in Australia and New Zealand

Abstract: Background: The number of vaginal breech and twin deliveries may be insufficient for adequate training. Objective: To determine whether advanced trainees and new Fellows in obstetrics are gaining adequate experience and confidence in vaginal breech and twin deliveries. Methods: An online survey was emailed to registered Royal Australia and New Zealand College of Obstetrics and Gynaecology (RANZCOG) advanced trainees and new Fellows (Years 1-5). This survey asked about their experience, confidence and whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
2
6
0
2
Order By: Relevance
“…34 35 Furthermore, among trainees who did not intend to offer vaginal breech deliveries and vaginal twin deliveries, in 46% and 67%, the argument was that they did not have sufficient experience to manage these complex vaginal deliveries. 35 A common feature of the events studied was that the time interval between emergencies or high-risk deliveries depended on the healthcare professional group, indicating that some groups can acquire the skills based primarily on clinical experience alone. However, alternative educational pathways should be provided for other groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…34 35 Furthermore, among trainees who did not intend to offer vaginal breech deliveries and vaginal twin deliveries, in 46% and 67%, the argument was that they did not have sufficient experience to manage these complex vaginal deliveries. 35 A common feature of the events studied was that the time interval between emergencies or high-risk deliveries depended on the healthcare professional group, indicating that some groups can acquire the skills based primarily on clinical experience alone. However, alternative educational pathways should be provided for other groups.…”
Section: Discussionmentioning
confidence: 97%
“… 34 35 Furthermore, among trainees who did not intend to offer vaginal breech deliveries and vaginal twin deliveries, in 46% and 67%, the argument was that they did not have sufficient experience to manage these complex vaginal deliveries. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The JUMODA study confirmed that planned CS (compared with planned vaginal delivery) for twins could be associated with increased composite neonatal mortality and morbidity, particularly when delivery was before 37 weeks 44 . Nevertheless, there is a strong preference among mothers with twin pregnancies for planned CS, which is likely to be compounded by the clinician's lack of confidence in conducting complex vaginal deliveries 45 . The high CS rate for twin pregnancies is unlikely to be reduced in the future.…”
Section: Category 8 (Multiple Pregnancies)mentioning
confidence: 99%
“…Since clinical expertise and teaching competency for vaginal breech delivery are generally dwindling, it is of high importance to promote the training of obstetricians in this clinical skill around the world. The quality and frequency of teaching how to deliver a baby out of breech presentation is improvable [ 17 , 18 ]. To amplify teaching of the management of vaginal breech delivery in an upright position, it is necessary to study delivery outcomes and learning curves of newly trained obstetricians and to take a closer look on the preexisting knowledge and training.…”
Section: Introductionmentioning
confidence: 99%